The effects of immunization with recombinant Sm14 (rSm14) in reducing worm burden and mortality of mice infected with Schistosoma mansoni - Fábio Ribeiro; Cristiane dos Santos Vieira; Adriana Fernandes; Neusa Araújo; Naftale Katz (Revista da Sociedade Brasileira de Medicina Tropical, 2002)
To investigate whether mice immunization with the recombinant form of a 14.7 KDa Schistosoma mansoni protein (rSm14) confers protection against a S. mansoni lethal challenge infection, rSm14-immunized mice were challenged with different cercarial burdens. A significant protection was detected in immunized mice challenged with 100 or 1,000 S. mansoni cercariae when compared with their controls (p< 0.004 and p< 0.01 respectively). Differently from previous report, none of the mice from the control group (not immunized and infected with 1000 cercariae) died before the 30th day post-infection. A direct correlation between the number of challenge cercariae and the precocity of mice death was found. IgM anti-rSm14 antibodies were significantly produced (p< 0.05) mainly in the groups of immunized mice infected with 500 or 1000 cercariae. IgG and IgA anti-rSm14 antibodies were not significantly detected. In Western immunoblots, all mice sera showed a specific antibody response with a 14.7 KDa antigen being reacted with particular intensity in sera from immunized mice. The results show that immunization with rSm14 reduced mice worm burden independently of the cercariae load of challenge infection. No correlation was found between serum antibodies and worm burden reduction. In relation to cercarial load and the rate and precocity of mice mortality a direct correlation was found.